Wheat Seed Germination After Low-Temperature Treatment or Ozonation - Kovalenko, Galyna; Strybul, Tamara; Rebrova, Nataliia; Shevchenko, Nadiia (Problems of Cryobiology and Cryomedicine, 2024)
The influence of pre-sowing treatment of Solomiya, Verden and Staleva winter wheat seeds either with ozonation or low temperatures (‒20, ‒40, ‒80 and ‒196°C) on their initial growth parameters was under study. The findings demonstrated a stimulating effect of ‒20 and ‒80°C on dynamics of seed germination and biometric parameters of seedlings for all the cultivars. The winter wheat seeds cooled down to ‒40°C showed virtually no changes in their germination rates compared to the control. Cooling down to ‒196°C worsened the germination of Solomiya seeds, decreasing the shoot length, dry weight of sprouts and roots as compared to the control. Verden and Staleva cultivars revealed the root elongation and accelerated seed germination. Ozonation caused no effect on dynamics of seed germination in all the studied wheat cultivars, except for Staleva, where some inhibition of germination was noted. According to biometric parameters, the root length increased in all the cultivars, and dry weight of sprouts was additionally augmented in Solomiya one. Probl Cryobiol Cryomed 2024; 34(2):113–124